2019
DOI: 10.1021/acs.nanolett.9b03642
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Piezoelectric Effect Derived from Grain Boundary in MoS2 Monolayers

Abstract: Recent discovery of piezoelectricity existed in two-dimensional (2D) layered materials represents a key milestone for flexible electronics, miniaturized and wearable devices. However, the so far reported piezoelectricity in these 2D layered materials is too weak to be used for any practical applications. In this work, we discovered that grain boundaries (GBs) in monolayer MoS 2 can significantly enhance its piezoelectric property. The output power of piezoelectric devices made of the butterflyshaped monolayer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
86
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(89 citation statements)
references
References 40 publications
0
86
0
2
Order By: Relevance
“…An increasing output piezoelectric current was investigated with the increase in strain rate. Interestingly, Dai et al [ 221 ] found that grain boundaries in monolayer MoS 2 can significantly enhance its piezoelectric property. The output power of piezoelectric nanogenerator made of the CVD-grown butterfly-shaped monolayer MoS 2 was 50% higher than the device made of triangular sample.…”
Section: Applications Of Strain-engineered 2d Semiconductorsmentioning
confidence: 99%
“…An increasing output piezoelectric current was investigated with the increase in strain rate. Interestingly, Dai et al [ 221 ] found that grain boundaries in monolayer MoS 2 can significantly enhance its piezoelectric property. The output power of piezoelectric nanogenerator made of the CVD-grown butterfly-shaped monolayer MoS 2 was 50% higher than the device made of triangular sample.…”
Section: Applications Of Strain-engineered 2d Semiconductorsmentioning
confidence: 99%
“…Recently, the emergence of photodetectors based on 2D materials has opened up an avenue to circumvent the abovementioned dilemma owing to their free surface dangling bonds. [ 13,14 ] In addition, 2D materials usually have atomic thickness, [ 15 ] high specific surface area, [ 16 ] and strong light‐matter interaction, [ 17 ] which can provide high responsivity and photoconductive gain in nanoscale photodetectors. [ 18–22 ] Such 2D materials currently cover a vast range of bandgaps from the terahertz in bilayer graphene, [ 23 ] visible in transition metal dichalcogenides to the ultraviolet in h‐BN and mica.…”
Section: Introductionmentioning
confidence: 99%
“…[5,12] Recently, the emergence of photodetectors based on 2D materials has opened up an avenue to circumvent the abovementioned dilemma owing to their free surface dangling bonds. [13,14] In addition, 2D materials usually have atomic thickness, [15] high specific surface area, [16] and strong light-matter interaction, [17] which can provide high responsivity and photoconductive gain in nanoscale photodetectors. [18][19][20][21][22] Such 2D materials Exploring 2D ultrawide bandgap semiconductors (UWBSs) will be conductive to the development of next-generation nanodevices, such as deep-ultraviolet photodetectors, single-photon emitters, and high-power flexible electronic devices.…”
mentioning
confidence: 99%
“…Piezoelectricity pushes forward 2D TMDs in nanosensor and nanogenerator applications because of their anisotropic piezoelectric coefficient and power output. [ 95 ] As reported by Kim et al., the piezoelectric coefficient of monolayer MoS 2 in the armchair direction is 3.78 pm V −1 , while that in the zigzag direction reaches 1.38 pm V −1 , revealing its anisotropic piezoelectric property and providing a new way harvesting mechanical energy in low power‐consuming devices and self‐powered electronics. [ 96 ] Stacking of 2H‐MoS 2 with even number of layers will eliminate piezoelectricity for centrosymmetry.…”
Section: Structure and Electrical Properties Of Phase Transition 2d Materialsmentioning
confidence: 88%